2021
DOI: 10.3390/biomedicines9070720
|View full text |Cite
|
Sign up to set email alerts
|

Towards Clinical Application of Artificial Intelligence in Ultrasound Imaging

Abstract: Artificial intelligence (AI) is being increasingly adopted in medical research and applications. Medical AI devices have continuously been approved by the Food and Drug Administration in the United States and the responsible institutions of other countries. Ultrasound (US) imaging is commonly used in an extensive range of medical fields. However, AI-based US imaging analysis and its clinical implementation have not progressed steadily compared to other medical imaging modalities. The characteristic issues of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 136 publications
(155 reference statements)
0
42
0
Order By: Relevance
“…A good correlation between the COVID-19 lung lesions as determined by CT parameters and the clinical and biochemical markers of multiple organs has been observed [46]. Harmon et al showed that a series of DL algorithms delivered acceptable performance metrics for the classification of chest CT images Ultrasound is an option for real-time point-of-care testing without radiation exposure in various medical fields [30]. Although lung ultrasound requires closer physical proximity of the examiner to the patient, the risk of COVID-19 cross-infection can be minimized when a plastic disposable cover and individually packaged ultrasound gel on a portable probe are used [34,40].…”
Section: Medical Imaging Analysismentioning
confidence: 93%
See 3 more Smart Citations
“…A good correlation between the COVID-19 lung lesions as determined by CT parameters and the clinical and biochemical markers of multiple organs has been observed [46]. Harmon et al showed that a series of DL algorithms delivered acceptable performance metrics for the classification of chest CT images Ultrasound is an option for real-time point-of-care testing without radiation exposure in various medical fields [30]. Although lung ultrasound requires closer physical proximity of the examiner to the patient, the risk of COVID-19 cross-infection can be minimized when a plastic disposable cover and individually packaged ultrasound gel on a portable probe are used [34,40].…”
Section: Medical Imaging Analysismentioning
confidence: 93%
“…This approach can be used to study disease progression and its influencing factors in a single patient [39]. Ultrasound is an option for real-time point-of-care testing without radiation exposure in various medical fields [30]. Although lung ultrasound requires closer physical proximity of the examiner to the patient, the risk of COVID-19 cross-infection can be minimized when a plastic disposable cover and individually packaged ultrasound gel on a portable probe are used [34,40].…”
Section: Medical Imaging Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the expectations for artificial intelligence (AI) have increased greatly, and machine learning (ML) technology has made remarkable progress, including the rise of deep learning technology [ 10 , 11 ]. It is important to note that ML has been actively used in the fields of medical and biological research [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], and it has already been used in actual clinical practice [ 24 , 25 , 26 ]. Single-cell analysis is another field in which ML techniques have been used to overcome challenges and make more effective use of its results.…”
Section: Introductionmentioning
confidence: 99%